The development of laser powder bed fused nano-TiC/NiTi superelastic composites with hierarchically heterogeneous microstructure and considerable tensile recoverable strain. (1st February 2023) - Ma, Chenglong; Ge, Qing; Yuan, Luhao; Gu, Dongdong; Dai, Donghua; Setchi, Rossitza; Wu, Meiping; Liu, Yu; Li, Dongya; Ma, Shuai; Peng, Xin; Fang, Ziyu
Abstract: In this study, we fabricated the TiC nanoparticles decorated NiTi-based superelastic composites via laser powder bed fusion (LPBF) technology. Different from reactionlessness between TiC and NiTi in the conventional processes, high energy density of laser beam triggered strong diffusion behavior of carbon atoms from TiC nanoparticles and resulted in the precipitation of TiCx and attendant Ni-rich even Ti-rich intermetallics. Interestingly, these nanoprecipitates distributed along the intricate network of connected dislocations, architecting a novel submicron-scale cellular reinforcement structure and facilitating the formation of a hierarchically heterogeneous microstructure. The migration and distribution of TiC nanoparticles as well as the forming mechanism of the submicron cellular reinforcement structure were then elaborated. The study indicated laser scanning speed had significant influence on the distribution of TiC nanoparticles, the size of cellular structure and the matrix grain orientation. At the optimized parameter, the LPBF-fabricated nano-TiC/NiTi composites exhibited a weak orientation texture along the building direction, finer cellular structure and a considerable steady recoverable strain of 2.3% at a maximum tensile loading of 300 MPa. Graphical abstract: Image 1